2017
DOI: 10.4172/2329-8731.1000150
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent HIV Care and Treatment in Uganda: Care Models, Best Practices and Innovations to Improve Services

Abstract: Background: The number of adolescents living with HIV (ALHIV) in Uganda is growing. Improving access to HIV services among this population requires a lot of innovation. This study describes service delivery models and innovations to improve access to HIV care and treatment services by adolescents in Uganda.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Asire and colleagues [12] assessed both private and public clinics in Uganda caring for YPLHIV and found that only 3% of healthcare facilities had a speci c health transition clinic (HTC) to support the transition from paediatric providers to adult providers. Additionally, Nyabigambo and colleagues [13]found that HTC use is less common in those who are older (age 20-24), male, live in rural locations, acquired HIV behaviorally, are not on antiretroviral therapy (ART), and have CD4 counts > 250.…”
Section: Introductionmentioning
confidence: 99%
“…Asire and colleagues [12] assessed both private and public clinics in Uganda caring for YPLHIV and found that only 3% of healthcare facilities had a speci c health transition clinic (HTC) to support the transition from paediatric providers to adult providers. Additionally, Nyabigambo and colleagues [13]found that HTC use is less common in those who are older (age 20-24), male, live in rural locations, acquired HIV behaviorally, are not on antiretroviral therapy (ART), and have CD4 counts > 250.…”
Section: Introductionmentioning
confidence: 99%
“…An explorative qualitative approach was utilised for this study using eighteen (18) focus group discussions. Data was collected from 9 health facilities in all the four regions of Uganda.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…The four-box or four quadrant approach takes a more practical and clinically oriented approach to ethical challenges. Within this framework, all ethical problems are analyzed in the context of four topics: medical indications, patient preferences, quality of life, and contextual features (that is social, economic, legal, and administrative) (18). Each topic can be approached through a set of speci c questions with the goal of identifying various circumstances of a given case and linking them to their underlying ethical principle.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…HIV prevalence is four times higher among young women compared to young men [5] increasing the risk for perinatal transmission. There is a growing number of adolescents and young adults with HIV who require the transfer of care from pediatric to adult providers; yet, globally, many young people experience barriers (e.g., infrastructure, staff training) that complicate this process [1,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…These studies do not reflect the challenges of HIV care in sub-Saharan Africa, given that limited-resources increases the complexity of transition and its evaluation. Asire and colleagues assessed both private and public clinics in Uganda caring for YPLHIV and found that only 3% of healthcare facilities had a specific health transition clinic (HTC) to support the transition from pediatric providers to adult providers [7]. Additionally, Nyabigambo and colleagues found that HTC use is less common in those who are older (age [20][21][22][23][24], male, live in rural locations, acquired HIV behaviorally, are not on antiretroviral therapy (ART), and have CD4 counts > 250 [9].…”
Section: Introductionmentioning
confidence: 99%